Building Early Childhood Character through KH. Wahid Hasyim Education Model at RA Ma’arif Metro - Fertiliana Dea, Leli; Saidun Anwar, M.; Choirudin, Choirudin; Yusuf, Muhammad; Wahyudi, Apri (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to analysis early childhood characters through KH. Wahid Hasyim education model at RA Ma’arif Metro. The study used a descriptive qualitative to describe the values of character education in various activities. This study explains KH. Wahid Hasyim’s character and its relevance to early childhood education. Application of character by KH. Wahid Hasyim consists of eight characters: religious, tolerant, independent, democratic, nationalism, love for the motherland, friendly or communicative, and fond of reading. KH. Wahid Hasyim’s framework is in line with the objectives of character education applied in early childhood education. Cultivation of character is given by example, programmed activities, habituation, and repetition in daily life. Instilling character values in early childhood hopes for children’s obedience and must be recognized and believed by children to feel these values are valid and beneficial to themselves and their environment.